(untitled) (Research, Society and Development, 2023)
This article addresses the topic of smartphone use in schools, analyzing the benefits, challenges, and the use of information technology as educational strategies related to this practice. With the advancement of mobile technology, smartphones have become widely used devices among students. This article presents studies and research that explore the benefits of smartphone use in learning, such as quick access to information, personalization of the educational process, and promotion of collaboration among students. However, challenges are also discussed, such as inappropriate usage, distraction, and security issues. Educational perspectives for the productive and responsible use of smartphones are highlighted, emphasizing the importance of clear school policies and educator involvement. The study aims to understand how students perceive and intend to use their smartphones, exploring factors that affect their behavioral interactions. The research uses the technology acceptance model and the theory of planned behavior as theoretical frameworks. A literature review was initially conducted on types and research methods, particularly focusing on the case study as a qualitative research strategy. Subsequently, a theoretical framework for the integrated stages of the case study, along with tests and tactics for study validation, was proposed. This involved using a questionnaire answered by students, observation, and data tabulation. The article concludes with reflections on the motivation of the results to promote conscious and healthy smartphone use among students.